CHARACTERISTICS MASK FORTIFIED MILK KEFIR CATTLE POWDER FLOWERS TELANG (Clitoriaternatea L.) POST INCUBATION - D. C., Raharjo; Lindawati, S. A.; Miwada, I N. S. (Jurnal Peternakan Tropika, 2022)
The purpose of this study was to determine the characteristics of fortified cow's milk kefir masks withpowdered telang flower after incubation. The research was carried out from February to April 2021 at the Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Science, Udayana University. The experimental design used was a completely randomized design (CRD) with four treatments and four replications, namely 0% fortification of telang flower powder (P0), 4% fortification of telang flower powder (P1), 6% fortification of telang flower powder (P2), fortification of 8 % of flower pollen (P3). The variables observed included pH, adhesion, phenol, flavonoid, color, texture. The results showed that the characteristics of fortified kefir masks had a pH value of P0 (4.74), P1 (4.86), P2 (4.97), and P3 (4.97) which were statistically significantly different (P<0 0.05), the adhesion to treatment P0 (23.67), P1 (15.46), P2 (12.36), and P3 (10.23) were statistically significantly different (P<0.05), phenol at treatments P0 (9.96), P1 (25.90), P2 (40.98), and P3 (46.86) were statistically significantly different (P<0.05), flavonoids in treatment P0 (146.97) , P1 (166.09), P2 (165.95), and P3 (170,22) were statistically significantly different (P<0.05), the color in the treatment P0 (white), P1 (light purple), P2 ( light purple), and P3 (purple) were statistically significantly different (P<0.05), the textures of the treatments P0 (liquid), P1 (liquid), P2 (slightly thick), and P3 (slightly thick) were statistically significantly different (P<0.05). The conclusion of this study that the kefir mask with fortification of telang flower after incubation affected the pH value, adhesion, total phenol, flavonoid, color, texture and fortification of 4% was able to provide the best characteristics. Keywords: kefir mask, cow's milk, mask characteristics and telang flower